PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN PMO PADA PASIEN GANGGUAN JIWA DI PUSKESMAS BOTUMOITO - Fitria Handayani; Ulfa Domili (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Insaneis a mental illness which is difficult to define. To support people who suffer with this illnes, member soft he family need to have knowledge in looking after those suffering people. Thus, health education is one of the efforts to create conducive atmosphere in a society. This researc his to analyze the influence of health education to words PMO oninsane patients in Botumoito Health Center. Pre-experimentis used as a design with pre-post test one group. The results hows that before giving thetreatment (healthedication) to the member so ffamily, there are 4 people (26,7%) categorized as people with good health education and 11 people (73,3%) are lack. After thetreatment, all participantss how excellen tunder stading of PMO (100%). It means that member so ffamily (participant) perform better under standing of PMO than before. There fore, it can be conclude that health education significant lynfluences on under standing on family members in PMO to the insan epatients.